Modeling and Control of Knee-Ankle-Toe Active Transfemoral Prosthesis - Chen, Yawei; Xuan, Bokai; Geng, Yanli; Ding, Sanbo; Chen, Lingling (IEEE access, 2020)
The main joints of lower limb are hip, knee, ankle, and toe. Because of accidents or diseases, some people have to amputate. Wearing prosthesis can help them return to normal life. In the past, Active Knee joint and Active Knee-Ankle transfemoral prosthesis are studied. While in the stance phase, toe joint play an important role. In this article, the dynamic model and control method of Knee-Ankle-Toe Active Transfemoral Prosthesis are studied. The main contents are as follows: Firstly, according to the ground reaction force, the gait cycle is divided into three phases, Early and Middle Stance Phase (E&MSP), Late Stance Phase (LSP) and Swing Phase (SP), and the mechanical model of Knee-Ankle-Toe Active Transfemoral Prosthesis (KATATP) is established. Secondly, consider the cooperative movement of amputee and prosthesis, the kinematics model of prosthesis is established by Lie Groups and Lie Algebras, and the dynamic model of prosthesis is established by Lagrange equation. Thirdly, the whole gait cycle is a complete system and each phase is a different subsystem, switching rules and controllers of different subsystems are designed. Finally, experiments show that KATAP with the switching control enables amputee to have a biomechanically appropriate walking gait and achieve smooth transition between different gait phases.